Integrasi Servqual Dan Ahp Untuk Evaluasi Kualitas Layanan Dekranasda (SAINTEKBU, 2021)
Achieving superior service quality is the main concern of all service providers, so that service providers are urged to provide high quality customer-oriented services. The purpose of this study was to analyze the quality of customer service at Dekranasda Rembang, using the Servqual and Analitycal Hierarchy Process (AHP) methods. Servqual is used to see customer perceptions and expectations on the five dimensions of servqual including Physical Evidence (Tangibles), guarantee (Reliability), Responsiveness (Responsiveness), Assurance (Assurance) and Empathy (Emphaty). While AHP is used to weight each dimension and criteria. The results showed that there were 10 service criteria that had to be improved immediately by Dekranasda, so as to improve customer quality.